Online room reservation and scheduling system for a hospital (ORRASH) / Lee Heng Siong - Lee , Heng Siong (2002)
Online Room Reservation and Scheduling System For A Hospital (ORRASH) is a system that help the medical staff (nurse, physician) in a hospital to book a room ( a bed of a ward, an operation room) and administrate room scheduling in an easy way by eliminate the conventional manual way. This system also provides the online patient information for the patient and medical staff to view the patient records using network. Before develop this system, an interview was made with the authority of a hospital to know the process of booking a room in the hospital and a research was made on a similar system in the Internet. The Waterfall model with prototyping was chooses as the project life cycle for this system. Microsoft Visual InterDev is selected as the development tool whereas the Internet Information Server 4.0 is the server and the back-end database is Microsoft SQL Server 7.0. Both servers are deployed on Windows 2000 Server platform. This system is divided into three modules. There are patient module, nurse module, and physician module. Each module will describe the function that can be done under the module. This system is important as it creates a new administration way to automate the process of booking room in a hospital. By using this system, the medical staff workload will be reduced and the mistake of booking a room, which is not available can be minimized.